2016
DOI: 10.1136/bcr-2016-215628
|View full text |Cite
|
Sign up to set email alerts
|

Acute ST elevation myocardial infarction in fulminant systemic p-ANCA vasculitis: a rare catastrophic complication

Abstract: A 45-year-old Caucasian man presented to the hospital with a 3-month history of fatigue, bilateral upper and lower limb paresthesias and gradually worsening ascending paralysis. A few weeks later, he developed acute renal failure requiring haemodialysis. Investigations revealed presence of myeloperoxidase (MPO) perinuclear antineutrophil cytoplasmic antibodies (ANCA). Renal biopsy was conclusive for rapidly progressive glomerulonephritis with crescents. Treatment for ANCA positive vasculitis was initiated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…( 3 ) demonstrated that patients with AAV carried an increased relative risk for all cardiovascular diseases. However, AAVs are predominantly small vessel diseases, and isolated coronary artery or valvular involvement is rare and mostly found incidentally on imaging or on autopsy ( 4 ). Only 2 cases of MPA with coronary involvement were reported in our literature review.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 3 ) demonstrated that patients with AAV carried an increased relative risk for all cardiovascular diseases. However, AAVs are predominantly small vessel diseases, and isolated coronary artery or valvular involvement is rare and mostly found incidentally on imaging or on autopsy ( 4 ). Only 2 cases of MPA with coronary involvement were reported in our literature review.…”
Section: Discussionmentioning
confidence: 99%
“…A Japanese autopsy report of a woman with MPA revealed scattered infarcts in the left ventricular wall and septum without coronary obstruction ( 5 ). The other case reported multiple distal coronary stenosis that could not go undergo intervention ( 4 ). Our case was the only reported case of MPA with isolated coronary and valvular involvement that required CABG.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular (CV) events are among the leading causes of death in AAV; thus, a more complex understanding of CV manifestations and their risk factors is required (4). In line, cardiac involvement is an underdiagnosed manifestation in AAV, and involvement of the coronary arteries is only rarely reported (5)(6)(7)(8)(9). Our case illustrates that myocardial infarction with non-obstructive coronary arteries (MINOCA) might be an important contributor to cardiac complications seen in patients with AAV and/or anti-GBM disease.…”
Section: Introductionmentioning
confidence: 99%